2008
DOI: 10.1007/s00405-008-0739-0
|View full text |Cite
|
Sign up to set email alerts
|

Sensorineural hearing loss in patients with chronic otitis media

Abstract: Objectives: Chronic otitis media is currently associated with an increase in air conduction thresholds. However, a few groups reported a decrease in sensorineural function in these patients. This study evaluates the occurrence of sensorineural hearing loss in patients with chronic otitis media.Methods: The records of patients with unilateral chronic otitis media were reviewed. Eighty-four patients met the inclusion criteria that were normal otoscopy and normal hearing in the contra lateral ear. Bone conduction… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
47
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 83 publications
(51 citation statements)
references
References 10 publications
3
47
0
1
Order By: Relevance
“…This study shows that chronic otitis media is associated with a decrease in cochlear function. (10) In our study some patients showed better bone conduction in the diseased ear, this agrees with finding of Dumich et al (1983). (6) CONCLUSION: The majority of patients with chronic suppurative otitis media had little difference in bone conduction between diseased and control ear, clinically significant sensorineural hearing loss is uncommon.…”
Section: Durationsupporting
confidence: 83%
“…This study shows that chronic otitis media is associated with a decrease in cochlear function. (10) In our study some patients showed better bone conduction in the diseased ear, this agrees with finding of Dumich et al (1983). (6) CONCLUSION: The majority of patients with chronic suppurative otitis media had little difference in bone conduction between diseased and control ear, clinically significant sensorineural hearing loss is uncommon.…”
Section: Durationsupporting
confidence: 83%
“…[4][5][6] It is generally believed that the passage of inflammatory mediators through the round window membrane into the scala tympani induced inner ear damage and SNHL. [7,8] MacArthur et al [9] suggested another point of view, that the inner ear could manifest a direct inflammatory response to COM resulting in SNHL.…”
Section: Discussionmentioning
confidence: 99%
“…However, the relationship between sensorineural hearing loss (SNHL) and CSOM remains a controversial issue. For instance, some workers have consistently reported the presence of SNHL in patients with this condition [6][7][8][9][10]. On the contrary, some investigators have reiterated the fact that little or no such relationship exist [11,12].…”
Section: Introductionmentioning
confidence: 99%